Acute pancreatitis following paracetamol overdose - Fernandes, Roland (BMJ Publishing Group, 2009)
A 17-year-old woman presented with acute abdominal pain and vomiting 3 h after she attempted to commit suicide by ingesting 30×500 mg paracetamol tablets. The woman was found to have a raised amylase level, and a CT scan confirmed the diagnosis of acute pancreatitis. According to the Naranjo adverse drug reaction probability scale, it is likely that the pancreatitis was induced by the paracetamol ingestion. A literature search reported 36 cases of pancreatitis following excessive doses of paracetamol, however this possible drug reaction is not widely recognised and not documented in the British National Formulary (BNF) list of possible adverse reactions from paracetamol. Being aware of the possibility that abdominal pain following paracetamol overdose may be a manifestation of pancreatitis can help the early detection and initiation of treatment for pancreatitis.